A ECONOMIC POLICIES FOR THE PROVISION OF ECONOMIC WELFARE IN REPUBLIC OF MACEDONIA - Loç, Elanur (International Scientific Journal Vision, 2017)
All the factors that determine a country’s economy can be listed as the most important economic determinants that each state should follow in order to possess the economic welfare. All those factors that can be counted such as; technological and regional development, development of the tourism sector, human capital investment, education, health, administrartive infrastructure and the quality of production, are the core factors supporting the country’s development. Since the economic growth it’s not enough by itself to provide the development of the economy, for the well-being of the societies, the public interventions must be taken into the consideration, referring to the technical knowledge and capacity-based policies. Taking in this regard, the Republic of Macedonia which is the one of the rapidly growing country in the recent years, must be considered for it’s development, such as, for creating additional employement, and for improving the leaving standard in the country. The aim of this work is to expose the main policies in the country that the government should follow for the provision of economic development. In addition to this, in terms of tourism sector which is listed among the needen interventions for development, in this paper will be talked about the development potential and prospects of the current tourism sector in Macedonia.